2024
DOI: 10.1007/s00003-023-01476-3
|View full text |Cite
|
Sign up to set email alerts
|

Food safety knowledge, attitudes, and practices of food vendors participating in Nigeria’s school feeding program

Bulus Barnabas,
Miroslava Bavorova,
Mustapha Yakubu Madaki
et al.

Abstract: This study aimed to measure the food safety knowledge, attitude, and practices among food vendors engaged in Nigeria’s ongoing Home-grown School Feeding Program. A cross-sectional survey was conducted in face-to-face interviews with 240 food vendors from 3 states in northeast Nigeria involved in the school feeding program using a structured questionnaire. Multiple linear regression results revealed that increased education and access to information through radio, television, and food inspection institutions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…A positive attitude is essential for food vendors to transmit knowledge into good practices [30,31,36]. However, some earlier studies [37][38][39] have also found similar results that practices and attitudes are related and different from knowledge, hence a worker with a good attitude would have better practice, but good knowledge is not necessarily translated to satisfactory practice. Poor level of attitude and practice could be attributed to the negligence and awareness of standard safety practices.…”
Section: Discussionmentioning
confidence: 99%
“…A positive attitude is essential for food vendors to transmit knowledge into good practices [30,31,36]. However, some earlier studies [37][38][39] have also found similar results that practices and attitudes are related and different from knowledge, hence a worker with a good attitude would have better practice, but good knowledge is not necessarily translated to satisfactory practice. Poor level of attitude and practice could be attributed to the negligence and awareness of standard safety practices.…”
Section: Discussionmentioning
confidence: 99%